Marcoscopic And Microscopic Motion Of Iron Oxide Magnetic Nanoparticles Stabilized Pickering Emulsion, Magnetophoresis At Low Field Gradient - Tham, Foo Kean (2020)
A magnetic responsive of magnetic Pickering emulsion (MPE) was synergistically stabilized by the iron oxide nanoparticles (IONPs) coated by poly(sodium 4-styrenesulfonate) (PSS) and cetrimonium bromide (CTAB) as well as the adjacent CTAB molecules. In this project, MPE, IONPs, IONPs-PSS and IONP-PSS-CTAB were synthesized with their chemical, physical and magnetism properties thoroughly characterized. The synthesized MPE was studied under two main scales: (1) macroscopic and (2) microscopic experiment for the motion of MPE. For macroscopic experiment, the changing of turbidity of the MPE suspension was recorded by a digital camera using intervalometer. Whereas, a bright field optical microscope was employed to study the microscopic behavior of the Pickering emulsion. All images analysis were performed by standard technique using Image J. At the macroscopic scale, the magnetic separation efficiency of MPE at 90 % was achieved within 30 minutes for all condition. However, the colloidal stability of MPE at pH 10 was the lowest as compared to pH 3 and deionized water conditions. MPE at pH 10 required the shortest time for achieving the highest separation efficiency. Hence, MPE at pH 10 experienced cooperative magnetophoresis as it could be irreversible flocculated during magnetophoresis. Besides that, the MPE didn’t deform and coalescence under the magnetic field, B of 0.26 T~0.66 T and magnetic field gradient (